Braving a super typhoon aftermath a narrative on the experiences of Yolanda survivors in Tacloban City - Ambal, Angelika O.; Chan, Shannon Francis E.; Collarga, Chenmarie Grace L.; Con-ui, Sherryjean Justin G. Uy (Angelika O. Ambal, 2014)
This study draws on qualitative data to know about the survival stories of Yolanda survivors in Tacloban City, determine their coping practices as they lived in the typhoon's aftermath, and understand how they made sense of the event that transpired. The participants for this study were identified using purposive sampling. Interviews were conducted and data were analyzed using narrative analysis. The results revealed that the participants coped in the typhoon's aftermath through: (a) self-help in the form of self-talks, looting, resumption of daily routines and; (b) social support received from family, friends and humanitarian aid from the government, local nongovernment, and international nongovernment organizations.